Static, fatigue and stress-shielding analysis of the use of different PEEK based materials as hip stem implants - Gok, Mustafa Guven (Walter de Gruyter GmbH, 2022)
Abstract There is a possibility that hip joints may become dysfunctional due to age, wear or some accidents, and in this case they need to be replaced with hip implants. However, after conventional hip stem implantation, the load transferred to the bone usually decreases due to the high stiffness of the metallic (most commonly Ti6Al4V, CoCr or stainless steel) hip stem implant, and as a result, mineral loss occurs in the bone which weakens. On the other hand, PEEK is an advantageous material with its low cost, ease of production, corrosion resistance and biocompatibility. More importantly, it has the potential to be a good alternative to metallic materials in load-bearing bone replacements, thanks to its mechanical properties and density close to that of the bone. In this study, hip stem implants having three different commercial PEEK materials and four different metallic main spar designs were modeled. Their behavior under static and dynamic loading conditions was analyzed according to ASTM-F2996-20 and ISO-7206-4:2010 standard test methods, and the stress-shielding effect of hip stems modeled as implanted into the femur was simulated using ANSYS commercial finite element analysis software. According to the results, it was observed that CFP based hip stem models meet the five million life time criteria and increase the stress on the femur bone by up to 57%.